Analisis Kualitas Udara Ambien Menggunakan Indeks Standar Pencemar Udara (ISPU) dan Korelasinya Terhadap Kesehatan Manusia di Area Pertambangan Timah Kabupaten Bangka - Purba, Robekca; Susanti, Susi (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to determine ambient air quality using the Air Pollution Standard Index (ISPU) and its correlation with human health. Sampling was conducted at 11 locations in PT Timah Tbk mining areas from May 10-12, 2023, measuring PM₁₀, PM₂.₅, SO₂, CO, O₃, and NO₂ according to SNI standards by IPB LJPKS. ISPU calculation used Peraturan Menteri Lingkungan Hidup dan Kehutanan nomor 14 tahun 2020 with linear interpolation. Results showed PM₁₀ (35.4±7.0 μg/m³), PM₂.₅ (16.4±3.2 μg/m³), SO₂ (21.2±5.8 μg/m³), NO₂ (33.8±10.3 μg/m³), CO (